Pregnancy in Woman with Spinal Cord Stimulator for Complex Regional Pain Syndrome: A Case Report and Review of the Literature - Yoo, Hyung Seok (The Korean Pain Society, 2010)
Spinal cord stimulation (SCS) is used to manage chronic pain syndromes and it is accepted a cost-effective therapy. Child-bearing women who had SCS become or choose to become pregnant despite these policies pregnancy is a relative contraindication. A 32-year-old woman had SCS as a treatment for the CRPS I of the left lower extremity. During various check up tests, we happen to find out that her serum beta-hCG was positive and confirmed pregnancy. SCS is not recommended in pregnancy because the effects of SCS on pregnancy and nursing mothers had not been confirmed. However, many female patients suffering from chronic pain may expect future pregnancy and we think that they must be informed about the possibility of pregnancy and the effects of SCS device implantation in the course of pregnancy. First of all, a good outcome requires a multidisciplinary team approach, including obstetrics, neonatology, pain medicine and anesthesia, as was used from an early pregnancy. Unfortunately, she had a misabortrion after 6 weeks.